2014
DOI: 10.1002/jnr.23461
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neurobiologic mechanisms of antiallodynic effect of warm water immersion therapy on persistent inflammatory pain

Abstract: Water immersion is widely used in physiotherapy and might relieve pain, probably by activating several distinct somatosensory modalities, including tactile, pressure, and thermal sensations. However, the endogenous mechanisms behind this effect remain poorly understood. This study examined whether warm water immersion therapy (WWIT) produces an antiallodynic effect in a model of localized inflammation and whether peripheral opioid, cannabinoid, and adenosine receptors are involved in this effect. Mice were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…The present meta-analysis also showed that exogenous ADO relieved postoperative pain by 24h, thereby reducing opioid requirements. These results were in accordance with the studies by Katz et al and Martins et al [26, 27] in that endogenous ADO production was found to improve mechanical hyperalgesia. The first postoperative analgesic requirement was about 25 times longer than in the remifentanil subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…The present meta-analysis also showed that exogenous ADO relieved postoperative pain by 24h, thereby reducing opioid requirements. These results were in accordance with the studies by Katz et al and Martins et al [26, 27] in that endogenous ADO production was found to improve mechanical hyperalgesia. The first postoperative analgesic requirement was about 25 times longer than in the remifentanil subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…Mice were injected (intraplantar [i.pl.]) with 20 µL 80% CFA ( Mycobacterium tuberculosis ) as described by Meotti et al 21 and Martins et al 22 CFA produced significant hindpaw swelling and hyperalgesia. To evaluate mechanical hyperalgesia, the animals were tested for response frequency to mechanical stimuli with calibrated von Frey filaments [VFFs] applied to the plantar aspect of the right hindpaw.…”
Section: Methodsmentioning
confidence: 98%
“…The right hindpaw was stimulated with a constant pressure of 0.4 g with the VFF (Stoelting). The response frequency to 10 applications was used as an indicator of nociceptive behavior, and the results are expressed as the percentage of withdrawal frequency 22 . Mechanical hyperalgesia tests were performed before (baseline) and 24 hours after i.pl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabapentin is also used to treat restless leg syndrome, which was recently reported to have a MoA involving the A 1 AR [85]. One of the more unusual proposals is a peripheral adenosinergic MoA of warm-water-immersion therapy for treating persistent inflammatory pain, based on the antagonism by locally administered DPCPX (10 nmol/paw) [86].…”
Section: Pain Antidepressant Sleep and Other Behavioral Interventionmentioning
confidence: 99%